EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN KONTEKSTUAL (CTL) DITINJAU DARI GAYA BELAJAR SISWA KELAS VII SMPN KOTA SURAKARTA - Kirana, Arinta Rara (Lentera: Jurnal Ilmiah Kependidikan, 2015)
The objectives of research were to find out: 1) which one providing better mathematics learning achievement, TTW by using CTL model, TPS by using CTL model or Learning directly, 2) which one providing better mathematics learning achievement, auditorial style, visual style or kinestetik style, 3) in each learning tyle level, which one providing better mathematics learning achievement, TTW by using CTL model, TPS by using CTL model or Learning directly, and 4) in each learning models, which one providing better mathematics learning achievement, auditorial style, visual style or kinestetik style. This research used the quasi experimental research method. The design of the research was 3 Ã— 3 factorial. The population was the students of the seven class of Junior High School in Surakarta City on academic year 2014/2015. The tecnique of sampling was stratified cluster random sampling.The proposed hypothesis of the research were tested by using the unbalanced two-way analysis of variance.The conclusions of this research were asfollows: 1) TTW by using CTL model provided better mathematics achievement than TPS by using CTL model and Learning directly. 2) thevisual style students had mathematics achievement better than auditorial style, the mathematics achievement of auditorial style is the same askinestetik style, and the visual style students had mathematics achievement better than kinestetik style. 3) in each of learning style categories, students mathematics learning achievement is in constancy with result of learning models.4) in each learning models, the students mathematics learning achievement is in constancy with result of learning style categories.